Gertrudis Segovia Álvarez: Between her Need to Write and her Oblivion - Sáez-Méndez, Leonor (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Gertrudis Segovia Álvarez is a writer enters into the difficulty with a feminine identity for which she neither finds nor is given an intellectual or emotional status of her own. Self-denial, the literary and recognition needs of a socially influential father, her marriage to a well-known doctor from Tenerife, the admiration of an audience of women who were torn between seclusion and the fervour of a castrating Catholicism, are some of the traits that helped to conceal her. The writer of poetry, children's stories and novels traced a literary, intellectual and emotional path that was soon cut short, despite her recognition. In this contribution we will analyse part of the unknown life of the author in the Islands.